H.I.V.E. Escape velocity - Walden, Mark (Simon & Schuster Books for Young Readers, 2012)
The leader of the Higher Institute of Villainous Education has been captured by a security force, and it's up to Otto to save him. First he must escape Nero's sinister replacement and the institute itself before facing the ultimate challenge of breaking into M16, something no villain has ever succeeded in doing.